2013
DOI: 10.1093/alcalc/agt168
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Use on Inhibitory Control (and Vice Versa) During Adolescence and Young Adulthood: A Review

Abstract: Poor inhibitory control can be both the cause and the consequence of excessive alcohol use. Adolescence and young adulthood may be a particularly vulnerable period due to (a) the weak or immature inhibitory functioning typical of this stage may contribute to the inability of the individual to control alcohol use and (b) alcohol consumption per se may alter or interrupt the proper development of inhibitory control leading to a reduced ability to regulate alcohol intake. Further longitudinal research is needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 137 publications
(133 reference statements)
4
73
1
8
Order By: Relevance
“…Inhibitory executive control in adolescent and young adult drinkers is of particular interest in understanding the acquisition and persistence of AUDs into adulthood (López-Caneda et al, 2013). Consistent with previous findings (Stevens et al, 2007), ICA identified three functional brain networks associated with successful response inhibition.…”
Section: Response Inhibition and Escalating Maxdrinkssupporting
confidence: 82%
“…Inhibitory executive control in adolescent and young adult drinkers is of particular interest in understanding the acquisition and persistence of AUDs into adulthood (López-Caneda et al, 2013). Consistent with previous findings (Stevens et al, 2007), ICA identified three functional brain networks associated with successful response inhibition.…”
Section: Response Inhibition and Escalating Maxdrinkssupporting
confidence: 82%
“…Research assessing impulsive behavior in humans through prepotent response inhibition tasks shows that performance in these tasks steadily improves (reduction in reaction times and commission errors rates) from childhood to young adulthood (Jaeger, 2013; López-Caneda et al, 2014) and starts to decrease in later adulthood (Votruba & Langenecker, 2013). Inhibitory control seems to start maturing at around age 14 (Fischer et al, 1997; Luna et al, 2004; Munoz et al, 1998).…”
Section: Impulsive Behavior Across the Lifespan: Implications For mentioning
confidence: 99%
“…Although the ability to suppress an automatic response begins to develop early in life, efficiency in the process continues to refine through the end of adolescence (Luna et al, 2004). The maturational changes on the adolescent brain, especially the prefrontal cortex, which is linked to prepotent response inhibition, may explain the maintenance of drug-seeking behaviors (López-Caneda et al, 2014). After a period of stabilization in young-to-middle adulthood, performance in prepotent response inhibition tasks starts decreasing in older adulthood.…”
Section: Impulsive Behavior Across the Lifespan: Implications For mentioning
confidence: 99%
“…Inhibition, or impulse control, may be a key cognitive feature involved in regulating substance use [25]. Inhibition is a type of executive functioning that refers to the ability to withhold a pre-potent response in order to select a more appropriate, goal-directed response [26, 27].…”
Section: Neural Features That Predate Adolescent Substance Usementioning
confidence: 99%